Turkey Wattle Temperature Response to Distinct Environmental Factors - AS Mendes; DJ Moura; GM Morello; TMR Carvalho; RR Sikorski (Brazilian Journal of Poultry Science, 2015)
ABSTRACT Rearing environmental conditions are important for turkey production, because this bird is particularly sensitive to heat stress. This study aimed at measuring the wattle temperature response of turkeys of three different ages (61, 96, and 131 days old) exposed to different combinations of dry bulb temperature, relative humidity, and wind speed ranges, as an indication of their physiological responses. The experiment was conducted with 42 male birds housed in a controlled environment chamber and exposed to different combinations of two air speed (WS) ranges (WS1 = 0.3-0.6 ms-1, considered low, and WS2 = 1.2-1.6 ms-1, considered high), dry bulb temperature (DBT) between 22 and 34 °C, and relative humidity (RH) between 40 to 90 %. The statistical analysis showed that WS, DBT, and RH significantly influenced wattle temperature of 61-d-old turkeys, while only WS and DBT influenced this response when turkeys were 96 days old. Furthermore, DBT was highly correlated with both low and high WS. In 131-day-old turkeys, WT response was virtually the same at both wind speed ranges when high DBT was applied. Turkey wattle temperature was influenced by wind speed, and was dependent on both environmental dry bulb temperature and relative humidity, as well as bird age.